Gerontology counseling competency model: exploring model elements through the lens of experienced counselors - Nik Jaafar, Nik Nazlan; Pau Kee; Ahmad, Aslina (EDUCATUM Journal of Social Sciences, 2024)
Counselors play a vital role in supporting the mental health and well-being of older adults by recognizing and respecting their unique needs. This research marks a significant milestone in developing a gerontology counseling competency model aimed at enhancing counselors’ professional proficiency. In this qualitative phase, interviews were conducted with fifteen counselors registered with the Malaysia Board of Counselors, selected using purposive sampling to identify essential elements for the model. By analyzing detailed narratives from semi-structured interviews, the study seeks to uncover key elements that support effective counseling practices for older adults. These elements, grounded in the counselors’ experiences, include a wide range of qualities crucial for managing the complexity of counseling older adults. The data analysis revealed that counselors require several essential elements in their practice, including professional knowledge, counseling skills, techniques and tools, attitude and values, spirituality, and counseling ethics. Upon the culmination of this research, the gerontology counseling competency model is expected to elevate the standards of professionalism among counselors specializing in this field, thereby fostering the mental health and overall well-being of older adults, in alignment with Malaysia’s National Policy for Older Persons.